Communication Strategies And Collaboration Of Malaysian ESL Learners In Oral Interaction - Ismail, Che Rushita @ Rushita (2012)
The study reported in this thesis is an analysis of the use of communication strategies and collaboration of Malaysian ESL learners in oral interaction. It examined how Malaysian ESL learners manage to communicate their message in second language face-to-face oral interaction when the intended target language lexical items or structures to express meaning are unavailable. More specifically, the study aimed to analyse how learners and interlocutors convey meaning through the use of communication strategies when the desired lexical items or structures are unavailable.